The impact of the Russia-Ukraine war on global supply chains: a systematic literature review - Sarwar, Dilshad; Rye, Sara (Frontiers in Sustainable Food Systems, 2025)
This systematic review examines the multifaceted impacts of the Russia-Ukraine war on global supply chains. Following PRISMA methodology, we analyze 22 peer-reviewed studies published between 2022 and 2025 to identify key disruption patterns, sectoral vulnerabilities, regional impacts, and adaptive strategies. Our findings reveal significant disruptions across food, energy, and critical materials sectors, with asymmetric regional vulnerabilities particularly affecting developing economies. The review identifies five major impact domains: (1) food security disruptions, (2) energy market volatility, (3) critical material shortages, (4) transportation bottlenecks, and (5) financial market responses. We document emerging adaptation strategies including supply diversification, strategic reserves development, and accelerated digitalization. The findings suggest permanent shifts in global supply chain configurations and trade relationships that will persist beyond the conflict’s resolution. This review contributes to both academic understanding of supply chain vulnerability to geopolitical shocks and provides practical insights for logistics professionals developing resilience strategies.